Knowledge, attitudes, practice, and public health education demand regarding PARI prevention: a cross-sectional study among Chinese undergraduates - Kong, Yuzhe; Zhu, Xiaoyi; Yang, Yang; Xu, Haitao; Ma, LingFeng; Zuo, Yu (Frontiers in Public Health, 2024)
Objectives The purpose of this study was to assess the level of knowledge, attitudes, and practices (KAP) of university students in China regarding the need for PARI and public health education. Methods A cross-sectional online and offline survey was conducted in China website through Wenjuanxing and in different cities such as Changsha Hunan Province, Shanghai, Chongqing and in different public scenarios, such as hospitals, universities, and commercial venues between September 1 and September 7, 2023, using a 28-question questionnaire designed and reviewed by multidisciplinary experts. Results A total of 4,096 respondents were recruited for this study, with 3,957 valid questionnaires. The mean knowledge score was 1.84 ± 0.52, the mean attitude score was 2.12 ± 0.51, and the mean practice score was 3.18 ± 0.55. Regression analyses found that: region, grade, school, and weekly anaerobic exercise time were influences on the knowledge score; region, grade, school, and weekly anaerobic exercise time were influences on the attitude score; region, grade, school attended, weekly anaerobic exercise time and weekly anaerobic exercise time as influences on the practice score. Subgroup analyses revealed that undergraduates from southern regions and 985 schools had higher knowledge attitude scores and lower practice scores. As the grade level increased, the knowledge and attitude scores showed a V-shaped trend and the behavior scores showed an inverted V-shaped trend. Correlation analysis found a positive correlation between knowledge and attitude scores, and a negative correlation between both and behavior, respectively. The public health education needs survey found that undergraduate students generally preferred guided instruction methods and content centered on the RICE principles, they preferred learning through books and pamphlets, and they were happy to see relevant content promoted in the campus environment. Conclusion This study shows that Chinese undergraduate students have less knowledge, neutral attitudes, and good behaviors regarding PARI prevention. Special attention should be paid to meeting the needs of undergraduate students for public health education to equip them with relevant knowledge so that they can better behave in PARI prevention.